Respons Pertumbuhan Dan Produksi Ketimun (Cucumis sativus L) Terhadap Sistem Pengolahan Tanah Dan Jarak Tanam - H. Hamzah; Pieter J Kunu; A. Rumakat (Faculty of Agriculture, Pattimura University, 2012)
Cucumber is consumed regularly by inhabitants of Buru District of the Maluku Province, and, its productivity needs to be optimized. Soil tillage and plant density in cucumber cultivation have Influences on competition for nutrient intake, water and light and hence affect plant yield. The aim of this field experiment was to study growth and yield responses of cucumber (Cucumis sativus L.) on different soil tillage systems and planting densities. The field experiment was arranged in a factorial Randomized Block Design to examine several tillage methods (one and two) and planting densities (25 x 25 cm, 40 x 40 cm and 45 x 55 cm). The experimental results showed that there was no effect of interaction between soil tillage and planting density on all variable observed. Single and double tillage methods increased fruit number, fruit diameter, fruit length, fruit weight and root length of cucumber, while planting density gave no effect on all variables measured. Therefore, either single or double tillages and any planting densities tested in this experiment could be recommended in cucumber cultivation in Buru District of Maluku Province.